PENINGKATAN KEMAMPUAN LITERASI MEMBACA MELALUI PERMAINAN TRADISIONAL ENGKLEK PADA ANAK KELOMPOK A DI TK MARDISIWI KALIBARU - Firda Ulfa; Nurhafit Kurniawan; Wedya Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study focuses on the low reading literacy skills of early childhood, especially in group A (ages 4-5 years), which is caused by the lack of a fun learning approach and in accordance with the developmental stage of children's language skills. This study aims to improve children's reading literacy skills through traditional games of engklek as a learning medium. This study uses the Classroom Action Research (CAR) method, which was carried out at Mardisiwi Kalibaru Kindergarten with research subjects of group A children. Data collection techniques were carried out through observation, documentation, and interviews. Data were analyzed qualitatively to determine the increase in children's reading literacy skills after applying engklek media. This study aims in general to improve the reading literacy skills of group A children (ages 4-5 years) through traditional engklek games. The specific objectives of this study are: 1. Describe the application of engklek games in literacy learning, Knowing the increase in the ability to recognize letters and words. Identifying children's responses and interests in traditional game-based learning activities